Analysis of the mobilization region of the broad host-range IncQ-like plasmid, pTC-F14, and its ability to interact with a related plasmid, pTF-FC2 - Van Zyl, Leonardo Joaquim (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2003.